Analisis Faktor-faktor yang Mempengaruhi Kepatuhan Ibu dalam Pemberian Imunisasi Dasar Lengkap (IDL) di Puskesmas Hamparan Perak Kecamatan Hamparan Perak Kabupaten Deli Serdang Tahun 2024 - Dessy Ratna Sari; Fawziyah Husna; Debby Chyntia Yun; Ariska Fauziyanti; Ninsah Mandala Putri Sembiring (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Basic immunization services for children in Indonesia have been integrated starting from Posyandu, Community Health Centers and hospitals, however the overall basic immunization coverage is still below the target set by the government. Data from the Hamparan Perak Community Health Center shows that coverage of all types of complete basic immunization did not reach the target, and Deli Serdang Regency with the lowest IDL coverage in North Sumatra Province is Deli Serdang Regency. Objective: This study aims to analyze the factors that influence maternal compliance in providing complete basic immunization in Hamparan Perak sub-district, Deli Serdang district. Method: The research used quantitative research methods with a cross sectional study design which was carried out in the work area of ​​the community health center in Hamparan Perak sub-district, Deli Serdang district, starting from preparing the thesis to obtaining research results. The population in this study were mothers aged ≥ 18 years in the working area of ​​the health center in Hamparan Perak sub-district, Deli Serdang district. The sampling technique used in this research is probability sampling using simple random sampling with a sample size of 73 respondents. Results: The results of the study showed a significant influence between knowledge (p=0.03) and maternal compliance in providing immunizations, and there was no influence between perception (p=0.47), quality of immunization services (p=0.10), number children (p=0.46), distance to health services (p=0.74) and maternal compliance in providing complete basic immunization in Hamparan Perak sub-district, Deli Serdang district. Conclusion: the factor that most influences maternal compliance in providing complete basic immunization is knowledge. Suggestion: It is necessary to increase the role of health workers in providing good information to the public about the importance of immunization for babies, and it is hoped that this can also increase the public's positive perception of immunization.